Hubungan Status Pekerjaan, Status Gravida, dan Kecemasan dengan Kejadian Hipertensi pada Ibu Hamil di Puskesmas Kalijudan, Kota Surabaya - Ruffa'ida, Fatwa (Jurnal Keperawatan Muhammadiyah, 2019)
Pregnancy is a vulnerable period for a woman. There are many factors at risk of endangering a mother's life from the beginning of pregnancy, childbirth, to the puerperium. The maternal mortality rate in Indonesia is still high, reaching 305 deaths per 100,000 live births. Hypertension is one of the causes of pregnancy complications that often occur. Hypertension cases in Indonesia were 26.5% (RISKESDAS, 2013) while in East Java cases of hypertension were recorded at 13.47% and in Surabaya 10.43% of the total population who had been tested for blood pressure. The purpose of this study was to determine the relationship between work status, gravida status, and anxiety with the incidence of hypertension in pregnant women at Kalijudan Health Center, Surabaya. This study was an observational study with a cross sectional approach. Sampling in this study used a total sampling technique which was obtained as many as 38 pregnant women respondents at Kalijudan Health Center, Surabaya. Data collection was obtained from interview questionnaires and the blood pressure data was taken according to the medical records when respondents were checking their blood pressure. The independent variables in this study were job status, gravida status, and anxiety. The dependent variable in this study was the incidence of hypertension in pregnant women. The results of this study were there was a relationship between gravida status and the incidence of hypertension in pregnant women (p = 0.011), while employment status (p = 0.314) and anxiety (p = 0.107) were not associated with the incidence of hypertension in pregnant women. The conclusion of this study is the characteristics of pregnant women respondents in Kalijudan Health Center dominated by pregnant women who work, have multigravida status, and have anxiety during pregnancy. Conducting IEC-based counseling on hypertension and routinely screening pregnant women is considered to be the right thing to reduce the incidence of hypertension in pregnant women